Safety and Immunogenicity of an mRNA-Based RSV Vaccine Including a 12-Month Booster in a Phase 1 Clinical Trial in Healthy Older Adults - Shaw, Christine A; Essink, Brandon; Harper, Charles; Mithani, Runa; Kapoor, Archana; Dhar, Rakesh; Wilson, Lauren; Guo, Ruiting; Panozzo, Catherine A; Wilson, Eleanor; Simorellis, Alana K; Reuter, Caroline; et al. (The Journal of infectious diseases, 2024)
Abstract Background An mRNA-based respiratory syncytial virus (RSV) vaccine, mRNA-1345, is under clinical investigation to address RSV disease burden in older adults. Methods Based on a randomized, observer-blind, placebo-controlled design, this phase 1 dose-ranging study evaluated the safety, reactogenicity, and immunogenicity of mRNA-1345 in adults aged 65 to 79 years. Participants were randomized to receive 1 dose of mRNA-1345 (12.5, 25, 50, 100, or 200 µg) or placebo and matched mRNA-1345 booster or placebo at 12 months. Results Overall, 298 participants received the first injection and 247 received the 12-month booster injection. mRNA-1345 was generally well tolerated after both injections, with the most frequently reported solicited adverse reactions being injection site pain, fatigue, headache, arthralgia, and myalgia. Reactogenicity was higher after the booster injection but with severity, time to onset, and duration similar to the first injection. A single mRNA-1345 injection boosted RSV-A and RSV-B neutralizing antibody titers and prefusion F binding antibody (preF bAb) concentrations at 1 month (geometric mean fold rises: RSV-A, 10.2–16.5; RSV-B, 5.3–12.5; preF bAb, 7.2–12.1). RSV antibody levels remained above baseline through 12 months, indicating immune persistence. A 12-month booster injection also increased RSV-A and RSV-B neutralizing antibody titers and preF bAb concentrations; titers after booster injection were numerically lower than those after the first dose, with overlapping 95% CIs. Conclusions mRNA-1345 was well tolerated and immunogenic following a single injection and a 12-month booster. Clinical Trials Registration NCT04528719 (ClinicalTrials.gov). Older adults and those with comorbidities are at increased risk of severe RSV. We assessed the safety and immunogenicity of mRNA-1345, an RSV vaccine, in adults aged 65 to 79 years. mRNA-1345 was well tolerated and immunogenic following a single injection and 12-month booster.